Involvement of Family Members and Nutrition Care Pattern of Positive Deviance - Ratnaningsih, Tri; Wahyuni, Chatarina Umbul; Notobroto, Hari Basuki; Adi, Annis Catur (Health Notions, 2018)
Nutritious food giving in under-fives to sustain the growth and development of under-fives optimally required the involvement of family members other than fathers. The purpose of this study was to determine the correlation between family members involvement with the mothers nutrition care pattern of poor families in the Mojokerto regency of East Java. This research design was using case control with case population of poor mother with healthy under-five and control population was poor mother with nutritious problem child. Number of case group samples 79 people and control group 41 people. Sampling technique with multi stage sampling. Data collection using questionnaires that have been tested the validity and reliability to 30 people. Data analysis using chi square statistic test. The results showed that the involvement of other family members in the positive deviance mothers was good as much as 35 people (44.30%). In non-positive mother deviance involvement of most other family members were less than 31 people (75.61%), chi square obtained p = 0,000 and value Î± = 0,05, meaning there was correlation of family member involvement with care pattern of positive deviance mother. The involvement of family members motivated mothers to provide a good nutritional food to under-five children.